Kepastian Hukum Hak Waris Anak Luar Kawin yang Disahkan atas Harta Warisan Tanah yang Dibatalkan oleh Pengadilan (Analisis Putusan Mahkamah Agung Nomor 942 K/PDT/2022) - Athaayaa Karista Palia Putri Yoriswan (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the legal position of a legitimated illegitimate child concerning inheritance rights to inherited land whose inheritance rights were revoked based on Supreme Court Decision Number 942 K/PDT/2022. This research employs a normative legal research method using a statute approach, a conceptual approach, and a case approach. The legal materials used consist of primary legal materials, including the Indonesian Civil Code, Law Number 1 of 1974 concerning Marriage, Government Regulation Number 24 of 1997 concerning Land Registration, Government Regulation Number 18 of 2021, and Supreme Court Decision Number 942 K/PDT/2022. Secondary legal materials were obtained from books, scientific journals, and literature relevant to inheritance law and land law. Data analysis was conducted qualitatively using a descriptive-analytical method. The results of the study indicate that an illegitimate child who has been legitimated through the subsequent marriage of both parents has the same legal position as a legitimate child based on Articles 272 and 277 of the Indonesian Civil Code, and thus is entitled to inherit from the deceased. In this case, Amin Sudartio, as a legitimated illegitimate child, has the status of a lawful heir of Budiman Sudartio. However, the inheritance rights to the land that was the subject of the dispute could not be realized because the court found that the land object could not be clearly proven due to the absence of land boundary descriptions in the Land Certificate serving as the basis for land ownership. Supreme Court Decision Number 942 K/PDT/2022 does not revoke Amin Sudartio's status as an heir, but it results in the non-fulfillment of inheritance rights over the disputed land object due to weaknesses in land administration evidence.